German economic will - Makki Kazim, Aqeel (Journal of Economics and Administrative Sciences, 2020)
The economic renaissance of Germany began in the mid-nineteenth century, specifically in the year 1848, with the emergence of industry in the east of the country and the creation of a railroad linking the east of the country with its west, and the state and industrial investors at that time adopting a savings approach at the expense of consumption, and thus the emergence of surplus savings and capital accumulation (the basis of economic growth). This helped the German industry to recover locally to cover the need of the local market without resorting to importing, that is, self-reliance in providing life requirements. And the Germans continued this approach, especially for capitalists and industrialists, until they reached a degree with which the local market became unable to absorb the huge amount of industrial production surplus, then they headed towards the global market because the local market was in a state of sufficiency and this production exported abroad was strongly echoed in The souls of different peoples of the world that have not yet known the industry, except for the United Kingdom since 1776, the United States since 1840, France 1845, Japan 1868, and the Scandinavian countries in 1910 all of that made German investors get more profits and thus their country was dependent on one of the most important traps. This applies to the taxes obtained from the owners of productive capital (a capitalist system) and will not continue after this case until Germany has reached a real economic risk represented by the diminishing of the initially limited raw materials it has, as we know that Germany lacks natural resources such as oil and gas and others, but despite this, it seemed this The country since more than 80 years since the emergence of the industrial revolution in the United Kingdom and the emergence of the writings of the eminent economist (Adam Smith) in the year 1776 and his famous book (The Wealth of Nations), with an industrial revolution that surpassed itself first, and the cradle of the industrial revolution (United Kingdom) second and tens of years Which introduced it in AD A fierce bankruptcy with its French and English opponents after that, in pursuit of the sources of the raw materials needed to ensure the continued rotation of the industrial wheel